Gender equality for whom? A critical frame analysis of the 2007 Swedish domestic services tax reform. (August 2015) - Spehar, Andrea
This article considers the motivations behind a 2007 reform in Sweden to implement a tax deduction on domestic services for households, and how the reform could be passed despite extensive political opposition to it. Critical framing analysis is used to argue that at least a partial explanation for the policy reform is to be found in the inherent limitations of the gender equality policy as hitherto pursued in the country, and in the way these limitations were framed in the political debates to push for the reform. The analysis draws upon public documents and records of parliamentary and media debates.